Comparing the efficacy of physical therapy interventions in Alzheimer’s disease: a network meta-analysis - Wu, Jiawen; Teng, Yunfei; Xie, Yaming; Xing, Shuangtao; Zhi, Songsong (Frontiers in Aging Neuroscience, 2025)
Alzheimer’s disease (AD) is a progressive and debilitating neurodegenerative disorder that significantly impairs cognitive function and daily living abilities, representing a major public health challenge. Given the multifactorial nature of AD, effective therapeutic interventions targeting both cognitive and functional decline are critical. This study aimed to conduct a comprehensive comparison of the therapeutic effects of music therapy, acupuncture therapy, game therapy, cognitive training therapy, and exercise therapy on AD patients through a network meta-analysis. Randomized controlled trials (RCTs) published up until 2024 were systematically retrieved from multiple databases. Data were extracted, including the first author, publication year, country, total sample size, mean participant age, type and duration of intervention, and outcome measures such as the Mini-Mental State Examination, Activities of Daily Living, and Alzheimer’s Disease Assessment Scale-Cognitive Subscale. Statistical analyses were performed using the RevMan 5.3 and Stata 17 software. The analysis included 52 RCTs with a total of 3,409 participants, offering a strong dataset. The results indicated that game therapy produced statistically significant improvements in mental state and daily living abilities, while acupuncture therapy yielded the most pronounced improvements in cognitive function among AD patients. Notably, the comparative efficacy of these interventions suggests that game therapy may offer short-term benefits, particularly for mental health and functional abilities, whereas acupuncture therapy demonstrated superior long-term cognitive enhancements. In conclusion, tailored physical and cognitive interventions such as game therapy and acupuncture therapy may hold significant potential in optimizing treatment outcomes for AD patients, with implications for both clinical practice and future research.